"Vrem o ţară ca afară!": How Contention in Romania Redefines State-Building through a Pro-European Discourse. Issue 1 (February 2021) - Gubernat, Ruxandra; Rammelt, Henry P.
This article belongs to a forthcoming special cluster, "Contention Politics and International Statebuilding in Southeast Europe" guest-edited by Nemanja Džuverovic, Julia Rone and Tom Junes. Massive protest waves, mainly led by younger citizens, appeared during the past years in Romania. Gubernat and Rammelt provide an analysis of the production of meaning by the "Romanian street" as a collective actor. They argue that "Vrem o ţară ca afară! (We want a country like abroad!)" became the leitmotif for important parts of the Romanian protests of the past eight years. For so doing, Gubernat and Rammelt analyze the discursive underpinnings and the constructed frames in recent protests in Romania. Their demonstration synthesizes a social phenomenon that appeared during the Roșia Montană protests of 2013, continued with the Colectiv protests of 2015 and was reconfirmed during the 2017–2018 anti-corruption protests: the dichotomy between the discursive appropriation of the West, as a benchmark of progress and social modernization and the "self-racism" manifested in these movements. The use of Frame Analysis and Critical Discourse Analysis for the study of these waves of protests enables them to show how the Western hegemonic discourse on state-building provides the cultural conditions for social action as well as it enables mobilizing agents to frame national discontent. "'Vrem o ţară ca afară!' Redefining state-building through a pro-European discourse in Romania" concludes that recent protests in Romania reproduce Western ideals of modern state and politics through a value-based discourse around the idea of belonging to Europe.